2013
DOI: 10.1177/0021998313509866
|View full text |Cite
|
Sign up to set email alerts
|

Stress analysis in carbon/epoxy composites using Lcr waves

Abstract: This work presents the application of an ultrasonic method to measure stresses in unidirectional carbon fiber composites with epoxy matrix (HexTow Õ AS4/Hexply Õ 8552). This kind of composite is largely employed as a structural material in the aeronautical industry. The ultrasonic method is based on the acoustoelastic principle, a principle that holds that wave speed is affected by variations in strain in the material. We employ critically refracted longitudinal waves (Lcr waves) and relate their time-of-fligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 20 publications
1
17
0
5
Order By: Relevance
“…Egle and Bray studied the sensitivity of ultrasonic waves and found that the Lcr wave velocity was most affected by stress but least affected by material texture, and they evaluated the mechanical bending stress in steel plates by changing the frequencies of ultrasonic probes . Dos Santos et al presented an application of the Lcr wave method to stress measurement in unidirectional carbon fibre composites and found that the Lcr wave speed was sensitive to the stress along the fibre direction but insensitive to any other direction. Javadi et al used the Lcr wave to measure the welding residual stress distribution and evaluated the through‐thickness distribution of stresses.…”
Section: Introductionsupporting
confidence: 53%
“…Egle and Bray studied the sensitivity of ultrasonic waves and found that the Lcr wave velocity was most affected by stress but least affected by material texture, and they evaluated the mechanical bending stress in steel plates by changing the frequencies of ultrasonic probes . Dos Santos et al presented an application of the Lcr wave method to stress measurement in unidirectional carbon fibre composites and found that the Lcr wave speed was sensitive to the stress along the fibre direction but insensitive to any other direction. Javadi et al used the Lcr wave to measure the welding residual stress distribution and evaluated the through‐thickness distribution of stresses.…”
Section: Introductionsupporting
confidence: 53%
“…However, as this research is based on a composite material with uniaxial stress, Equation (1) can be applied in composites-only for uniaxial stress. Auteliano has applied equations for isotropic materials by using ultrasonic critically refracted longitudinal waves to investigate the uniaxial stress in carbon fiber composites with epoxy matrix [10].…”
Section: Acoustoelastic Effectmentioning
confidence: 99%
“…These include the hole-drilling method, ring core method, slot-cutting method, indentation method, layer removal method, etc. The non-destructive methods are based on the relationship between the internal stress and physical parameters, and include five main methods: X-ray diffraction method and neutron diffraction method, based on the evaluation of interplanar spacing in crystal materials [9]; the magnetic method, based on the magnetostriction effect in ferromagnetic materials [10]; the photoelasticity method, based on the birefringence exhibited by certain transparent materials [10]; the ultrasonic method, based on the relationship between stress and ultrasonic wave velocity [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 L cr waves have been used to measure residual stress generated during welding, [3][4][5][6] residual stress in railroad wheels, 7 and applied stress in composite materials. 8 Measurement of magnetic Barkhausen noise (MBN) is another NDT technique that can be used to evaluate stresses in ferromagnetic metals, such as steels. This new technique has been studied for the last two decades, and suitable applications, equipment, and measuring procedures are currently being investigated by researchers.…”
Section: Introductionmentioning
confidence: 99%